2020
DOI: 10.1002/cbic.202000682
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Cyclisation Mechanism for the Diterpene Spiroviolene and Investigations of Its Mass Spectrometric Fragmentation

Abstract: The diterpene spiroviolene, its diterpene synthase from Streptomyces violens and the experimentally determined terpene cyclisation mechanism were reported in 2017. Recently, the structure of spiroviolene was revised based on a total synthesis, with consequences for the cyclisation mechanism. Herein, a reinvestigation of the terpene cyclisation to spiroviolene and the mass spectrometric fragmentation mechanism investigated by 13C‐labelling experiments are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Taken together, our results can explain how both extant and reconstructed ancestral SvS can act as dual functioning sesqui-/diterpene cyclases. The described diterpene reaction mechanism 4 , 58 involves major charge rearrangements ( Figure 4 ), which requires aromatic residues to sequentially stabilize the intermediate cations via π-interactions on both walls of the binding pocket (such as Trp79, Trp82, Phe84, and Trp156 on helices C/F and Phe59 and Trp308 on helices B/K), whereas the sesquiterpene reaction mechanism occurs in a more focused region of the active site. Interestingly, the tryptophan corresponding to Trp308 that we propose to be involved in the diterpene formation, is conserved in SdS and HecS, which are both sesquiterpene cyclases, even though a direct involvement of this tryptophan in the sesquiterpene reaction mechanism has been excluded.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, our results can explain how both extant and reconstructed ancestral SvS can act as dual functioning sesqui-/diterpene cyclases. The described diterpene reaction mechanism 4 , 58 involves major charge rearrangements ( Figure 4 ), which requires aromatic residues to sequentially stabilize the intermediate cations via π-interactions on both walls of the binding pocket (such as Trp79, Trp82, Phe84, and Trp156 on helices C/F and Phe59 and Trp308 on helices B/K), whereas the sesquiterpene reaction mechanism occurs in a more focused region of the active site. Interestingly, the tryptophan corresponding to Trp308 that we propose to be involved in the diterpene formation, is conserved in SdS and HecS, which are both sesquiterpene cyclases, even though a direct involvement of this tryptophan in the sesquiterpene reaction mechanism has been excluded.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Visual inspection shows that formation of 7′ from 6 would be feasible. Alternative mechanistic steps for the generation of 7′ from 3 were also very recently proposed …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, the stereochemistry of spiroviolene was revised by Snyder and colleagues on the basis of their total synthesis. 6) Then in 2021, Xu and Dickschat performed a mechanistic investigation of spiroviolene biosynthesis by means of stereoselective labeling experiments, and revised the biosynthetic pathway 7) (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Spiroviolene synthase, a type I DTS from S. violens NRRL ISP‐5597, was found to convert GGPP into spiroviolene ( 133 ) by in vitro enzyme assays, [61] and the formation mechanisms of 119 and 133 were further investigated by isotopic labelling experiments [61] . The stereochemical assignment of 133 has been revised based on a combination of total synthesis and investigations into the cyclization mechanism [64] . Characterization of spata‐13,17‐diene synthase (SpS), a type I DTS from S. xinghaiensis S187, demonstrated that it could convert GGPP into the main compound spata‐13,17‐diene ( 134 ), which has a 5–4–5 tricyclic skeleton, and the side compound prenylkelsoene ( 135 ), which has a 4–5–5 tricyclic skeleton [65] .…”
Section: Structures Of Diterpenoids From Streptomycesmentioning
confidence: 99%